Reactivity of carbon black diamond electrode during the electro-oxidation of Remazol Brilliant Blue R - Ajeel, M.A.; Aroua, M.K.; Daud, W.M.A.W. (Royal Society of Chemistry, 2016)
This article reports for the first time, the reactivity of Carbon Black Diamond (CBD) electrode using cyclic voltammetry and electrochemical impedance techniques in 0.25 M H2SO4 solution containing 0.5 mM K4Fe(CN)6. Three CBD electrodes with different content of carbon black 5% (5CBD), 10% (10CBD), and 20% (20CBD) were used in this study. The reactions of the CBD electrodes were quasi-reversible while the 5CBD electrode had the best activity compared to 10CBD and 20CBD electrodes. The anodic oxidation behavior of Remazol Brilliant Blue R (RBBR) was investigated by using cyclic voltammetry and electrochemical impedance techniques on the 5CBD electrode in different pH solutions. The results indicated that the RBBR oxidized at 1.3 V, and the electro-oxidation process was more active in the low pH solution. Furthermore, the removal rate of RBBR on 5CBD attained 99.5% after 4 hours of the electro-oxidation process.